Modified H -Transform and Pathway Fractional Integral Operator (Global Journal of Science Frontier Research, 2012)
In this paper we have established a theorem wherein we have obtained the image of modified H-transform under the pathway fractional integral operator defined by Nair [8]. Three corollaries of the main theorem have been derived. Our findings provide interesting unification and extension of number of (new and known) results.
Keywords: Pathway fractional integral operator; modified H-function transform; H-function of one variable; Whittaker function; Wrights generalized Bessel fun